A educação em István Mészáros: reflexões por uma prática educacional transformadora - Brandão, Daniel Silva (2022)
The present work aims to analyze the conception of education of István Mészáros from his theorizations, conceptions and educational understandings in Education beyond capital (2005), in order to reflect on the construction of a transformative educational practice, such as a sustainable alternative. It starts from the need to perceive an urgent change in the hegemonic social structure based on education. Considers in this broad debate the state, function and theoretical-educational search for postulating an authentic conception, far from the coercive limits of capital, as well as fulfilling the historical objectives attributed to education, whether formal, informal or non-formal. In this conflict, he understands that to institute a radical change, it is necessary to reflect on the critique of the socio-metabolic organism of capital, in addition to building a critique that seeks to break with the incorrigible logic of capital, bearing in mind the real objectives of education: human emancipation.